2004
DOI: 10.2337/diacare.27.3.770
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Oral Tumors in Hungary

Abstract: OBJECTIVE -Numerous publications have already demonstrated that diabetes is a risk factor for the development of periodontal diseases and various inflammatory lesions in the oral mucosa. A possible correlation between diabetes and oral premalignancies and tumors was examined in this study, as no literature data are available concerning this problem.RESEARCH DESIGN AND METHODS -Stomato-oncological screening was carried out on 200 diabetic patients in the medical departments; the control group included 280 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 31 publications
4
46
1
16
Order By: Relevance
“…Epidemiological studies have indicated that type 1 and type 2 diabetes are risk factors for oral premalignant lesions such as leukoplakia and oral SCC (Ujpal et al 2004). In experimental animals, type 1 diabetes possibly increases the risk of oral SCC according to chemical carcinogenesis studies (Vairaktaris et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that type 1 and type 2 diabetes are risk factors for oral premalignant lesions such as leukoplakia and oral SCC (Ujpal et al 2004). In experimental animals, type 1 diabetes possibly increases the risk of oral SCC according to chemical carcinogenesis studies (Vairaktaris et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While the clinical analysis and the present finding showed the impact of DM as a strong prognostic factor for survival of HNSCC patients after curative surgical intervention [16,24], the DM-mediated modulations for HNSCC development were also evident in a number of previous studies. Early investigations found that the Oral Leukoplakia (OL) prevalence was higher in DM patients than in non-DM subjects (6.2% vs 2.2%) [65].…”
Section: Dmmentioning
confidence: 76%
“…While various factors including alcohol consumption, smoking, areca nut chewing and infection of oncogenic human papillomavirus type 16 (HPV16) could trigger aberrant genetic accumulation, defective epigenetic regulation and tumorous microenvironment resulting in pathological transformation during head and neck carcinogenesis [20][21][22][23], the association between imbalanced metabolism, such as DM, and HNSCC development is less emphasized. A retrospective analysis for more than 600 patients with oral squamous cell carcinoma (OSCC) and 574 control cases demonstrated that DM is more frequently detected in the oral cancer group than in the control group (24.3% vs 11.1%) [24]. More recently, it was found that DM patients with OSCC tend to have poorer prognosis based on the detection of a lower overall survival, recurrence-free survival and cancer-specific survival rates compared with non-DM patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…E két betegség patogenezisében számos hasonló té-nyező játszik szerepet és hasonló elváltozások alakulnak ki. Az utóbbi évek statisztikai vizsgálatai megállapítot-ták, hogy a diabetes mellitussal összefüggésben számos más szájbetegség is gyakrabban fordul elő: nyelvatrófi ás elváltozások, glossitis [19,20], fogágybetegség [21], szenzoros elváltozások, például szájégés, ízlelészavar [22], leukoplakia, lichen oris planus [21] és tumorok [23,24]. Az objektív tünetek közül gyakori a diffúz erythema, különösen a nyelven.…”
Section: Innervation Of Papilla Vallata In Diabetic Ratsunclassified